Perioperative low-dose ketamine improves postoperative analgesia following Cesarean delivery with general anesthesia. (18th March 2016) - Haliloglu, Murat; Ozdemir, Mehtap; Uzture, Neslihan; Cenksoy, Pinar Ozcan; Bakan, Nurten
Abstract: Objective : In this study, the effect of perioperative uses of low dose ketamine on post-operative wound pain and analgesic consumption in patients undergoing elective Cesarean section was evaluated. Methods : In randomized, double blind clinical trial, 52 women with American Society of Anesthesiologists (ASA) class I-II identification undergoing elective Cesarean section in general anesthesia were enrolled. In the ketamine group (group K), a ketamine bolus of 0.5 mg kg −1 IV was administered at the time of induction of general anesthesia. After induction, a ketamine infusion of 0.25 mg kg −1 h −1 was started and discontinued at the end of surgery. Patients allocated to the control group (group C) were given identical volumes of saline. The cumulative dose of morphine consumption after surgery was measured as the primary outcome of this study. Secondary outcomes were pain control assessed by numeric rating scale (NRS) and need for rescue analgesia and incidence of side effects. Results : The mean 24-h morphine consumption was lower in group K ( p = 0, 001). At 15 min postoperatively, NRS values were lower in group K than group C ( p = 0, 001). There was no difference among groups regarding the need for supplemental analgesia (rescue diclofenac doses) ( p > 0.05). Conclusions : Perioperative uses of low dose ketamine decreased post-operative opioid requirements, which was observed long after the normal expected duration of ketamine.